Construction of Ideology, Discursive Practices, and Power Relations in the Text of Kapatu Mbojo (Pantun Bima) as a Representation of Bima Culture - Sandi Rahmawati; Anwar Efendi (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
This research aims to uncover and analyze the relationship between ideology, discursive practices, and the use of language styles in Kapatu Mbojo (Pantun Bima) as a form of cultural representation of the Bima community. As an oral tradition rich in values, Bima Pantun is not merely a product of linguistic aesthetics, but a space for the contestation of meaning and a reflection of dynamic social structures. This study employs a qualitative approach using the framework of Critical Discourse Analysis (CDA) based on Norman Fairclough's three-dimensional model, integrating textual (micro), discursive practice (meso), and socio-cultural practice (macro) dimensions of analysis. Data were drawn from the book "Galeri Pantun Bima-Dompu" by Alan Malingi and from interviews with three Bima pantun practitioners (pematu), covering eleven pantun texts. Through textual analysis, it was found that Bima Pantun is dominated by the use of natural metaphors and personifications that reflect the community's deep connection to their environment. At the level of discursive practice, this pantun functions as a medium for transmitting moral values, social criticism, and a tool for legitimizing customary norms that are produced and consumed collectively. Ideologically, the study reveals a strong representation of religious-cultural values and certain social structures used to maintain harmony while affirming the cultural identity of the Mbojo community. This research concludes that Pantun Bima is an effective discursive instrument in representing cultural identity and maintaining the ideological stability of the Bima community amidst changing times. Penelitian ini bertujuan untuk membongkar dan menguraikan relasi keterkaitan antara ideologi, praktik diskursif, dan penggunaan gaya bahasa dalam Kapatu Mbojo (Pantun Bima) sebagai representasi budaya pada masyarakat Bima. Sebagai warisan tradisi lisan yang sarat nilai, Pantun Bima bukan sekadar hiasan estetika linguistik semata, melainkan wadah kontestasi makna dan cerminan struktur sosial yang dinamis. Penelitian ini menggunakan pendekatan kualitatif dengan kerangka Analisis Wacana Kritis (AWK) model Norman Fairclough yang mengintegrasikan tiga dimensi analisis: dimensi tekstual (mikro), praktik diskursif (meso), dan praktik sosiokultural (makro). Data diambil dari buku "Galeri Pantun Bima-Dompu" karya Alan Malingi dan hasil wawancara dengan tiga orang pematu bahasa Bima, mencakup sebelas teks pantun. Melalui analisis tekstual, ditemukan bahwa Pantun Bima didominasi penggunaan metafora alam dan personifikasi yang mencerminkan kedekatan mendalam masyarakat dengan lingkungannya. Pada level praktik diskursif, pantun berfungsi sebagai media transmisi nilai moral, kritik sosial, serta alat legitimasi norma adat yang diproduksi dan dikonsumsi secara kolektif. Secara ideologis, terdapat representasi kuat dari nilai religius-kultural dan struktur sosial tertentu yang digunakan untuk mempertahankan harmoni sekaligus menegaskan identitas budaya Mbojo. Penelitian ini menyimpulkan bahwa Pantun Bima merupakan instrumen diskursif yang efektif dalam merepresentasikan jati diri budaya serta menjaga stabilitas ideologi masyarakat Bima di tengah arus perubahan zaman.